2019
DOI: 10.1111/jeb.13491
|View full text |Cite
|
Sign up to set email alerts
|

Limits to environmental masking of genetic quality in sexual signals

Abstract: There is considerable debate over the value of male sexual ornaments as signals of genetic quality. Studies alternately report that environmental variation enhances or diminishes the genetic signal, or leads to crossover where genotypes perform well in one environment but poorly in another. A unified understanding is lacking. We conduct a novel experimental test examining the dual effects of distinct categories of genetic (inbred vs. crossed parental lines) and environmental quality (low, through high to extre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…However, when the whole population experiences a reduction in the resources available for reproduction, whether the opportunity for selection increases will largely depend on the effect of resources on the variance in the expression of sexually selected traits, rather than on their mean (Arbuthnott & Whitlock 2018;Fox et al 2019a). With a few notable exceptions (David et al 2000;Howie et al 2019), studies that test for condition dependence in sexually selected traits tend to focus on trait means rather than variances (Jennions et al 2001;Cotton et al 2004). Our study reveals remarkable concordance between the effects of resource limitation on specific trait means and variances (reduction in mean, increase in variance) and concomitantly the opportunity, relative importance, and patterns of pre-and postcopulatory sexual selection, which together point to patterns of heightened directional selection on condition-dependent traits under dietary stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the whole population experiences a reduction in the resources available for reproduction, whether the opportunity for selection increases will largely depend on the effect of resources on the variance in the expression of sexually selected traits, rather than on their mean (Arbuthnott & Whitlock 2018;Fox et al 2019a). With a few notable exceptions (David et al 2000;Howie et al 2019), studies that test for condition dependence in sexually selected traits tend to focus on trait means rather than variances (Jennions et al 2001;Cotton et al 2004). Our study reveals remarkable concordance between the effects of resource limitation on specific trait means and variances (reduction in mean, increase in variance) and concomitantly the opportunity, relative importance, and patterns of pre-and postcopulatory sexual selection, which together point to patterns of heightened directional selection on condition-dependent traits under dietary stress.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this effect could potentially be reversed if female mating rate is lower under harsh environmental conditions, thus reducing the scope for competition to continue after mating and possibly increasing selection on precopulatory traits (Perry et al 2009). Furthermore, the opportunity for sexual selection will depend on the effect of resource availability on the variance in male sexually selected traits, rather than on their mean, yet we know little about how environmental conditions influence variances in sexually selected traits (David et al 2000;Howie et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The main evidence for a deleterious effect of X SR on fitness is the reduced eyespan of SR males [47,50]. Male eyespan is an exaggerated, highly condition-dependent trait used in female mate choice [47,57], as well as signalling between males [58,59], which reflects male genetic and phenotypic quality [57,60,61]. However, in a series of experiments, Wilkinson et al [62] found little direct evidence that SR reduces fitness components.…”
Section: Introductionmentioning
confidence: 99%
“…The ‘high’ stress treatment was chosen using previous work, at a level at which eyespan substantially declined but before any large increase in mortality (Cotton et al., 2004b). Previous work has also shown that genetic differences in the male sexual ornament are constrained under low stress but amplified as environmental stress increases (Bellamy et al., 2013; David et al., 2000; Howie et al., 2019). This is not the pattern observed here as the smaller eyespan of SR males was consistent across environmental stress treatments (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…In the wild, females prefer to roost and mate with males with larger eyespan, both in absolute terms and relative to body size (Cotton et al., 2010; Wilkinson & Reillo, 1994). Male eyespan is highly sensitive to both a range of environmental (Bjorksten et al., 2001; Cotton et al., 2004a; David et al., 1998) and genetic stresses (Bellamy et al., 2013; David et al., 2000; Howie et al., 2019).…”
Section: Introductionmentioning
confidence: 99%